Optimization of workforce scheduling using integer goal programming approach / Norwaziah Mahmud ... [et al.] - Mahmud, Norwaziah; Jamaluddin, Siti Hafawati; Hamidun, Intan Syafina; Muhammat Pazil, Nur Syuhada (Universiti Teknologi MARA, Perlis, 2018)
Crisis of large number of workers suffered from stress at workplace is a real global world issue either in local or international country. This is due to the long working hours, inappropriate rest or leisure times and imbalance wages. Thus, appropriate worker scheduling should be well organize in order to have job satisfaction among all workers. Scheduling is defined as the allocation of resources to task over time in such a way that a limited performance measure is optimized. This research proposed a model of Integer Goal Programming which intends to optimize the staff scheduling that are related to the staff requirements by the company and staff preferences. Three main constraints encountered in the model are hard constraints, soft constraints and logical constraints. The objective function is to allocate staff in order to have balance work schedule at the optimal work hours and at the mean time to ensure the employee satisfaction and efficiency of workloads. Lastly, the pattern of scheduling will be rotated efficiently among the staff and each staff will be working according to each schedule pattern. The result from this study gives optimum solution in which are supported by software LINGO and Excel are presented and discussed based on the optimal staff schedule. Lastly, the pattern of scheduling will be rotated efficiently among the staff and each staff will be working according to each schedule pattern. With this cyclical scheduling, it gives staff more control over their work life because they know the type of shift schedule in future should have positive effect on their job satisfaction.